2021
DOI: 10.1007/s12144-021-01902-5
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression in women hospitalized due to high-risk pregnancy: An integrative quantitative and qualitative study

Abstract: Literature has shown that hospitalized women with high-risk pregnancy tend to develop anxious and depressive symptoms. Research has used quantitative or qualitative methods. By integrating both quantitative and qualitative methods, this study aims to analyze: a) the level of depression, anxiety, and pregnancy-related anxiety in a group of women hospitalized with high-risk pregnancy (hospitalized high-risk) compared with a group of non-hospitalized women with low-risk pregnancy; b) the content of hospitalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
1
0
5
Order By: Relevance
“…Another study with hospitalized high-risk pregnant women reported that low-risk pregnant women had a higher concern regarding own appearance. 27 Different results between studies are thought to be affected by other variables. The inclusion of high-risk pregnant women, both hospitalized and outpatient may have affected our study results.…”
Section: Discussionmentioning
confidence: 99%
“…Another study with hospitalized high-risk pregnant women reported that low-risk pregnant women had a higher concern regarding own appearance. 27 Different results between studies are thought to be affected by other variables. The inclusion of high-risk pregnant women, both hospitalized and outpatient may have affected our study results.…”
Section: Discussionmentioning
confidence: 99%
“…Gebelik kadın hayatını fizyolojik ve sosyo-psikolojik yönden etkileyen önemli bir dönemdir (1). Yüksek riskli gebelik annenin, fetüsün veya yenidoğanın ölüm, sakatlık veya hastalık riskinin yüksek olduğu durum olarak tanımlanır (2,3). Gebelik sırasındaki yüksek riskli durumlar önceden var olan (obezite, hipertansiyon, diyabet vb.)…”
Section: Introductionunclassified
“…veya ilk olarak gebelik sırasında ortaya çıkan bir tıbbi duruma bağlı olabilir (2). Yüksek riskli gebelik olarak tanımlanan bu tıbbi durumlar arasında en yaygın preeklampsi, gestasyonel diyabet, plasenta anomalileri, erken membran rüptürü ve erken doğum riski görülmektedir (2,3). Williamson ve ark.…”
Section: Introductionunclassified
See 2 more Smart Citations